Emergency injury treatment for UiTM student by using courseware / Masita Zainon - Zainon, Masita (2020)
Emergency Injury Treatment (EIT) courseware is a multimedia application which is designed to provide the student the knowledge of the treatment. This courseware is a platform awareness of injury treatment towards student. Recent based on survey to 46 student shows that most student do not have knowledge of the injury treatment. This happen due to many contributing factors. One of them, not aware to the earth surface when walking. The objectives of proposed project are to develop the student treatment knowledge using multimedia element in the courseware. Secondly is to evaluate the heuristic evaluation for the expert and effectiveness of application whether UiTM student can treat the injury through question. This courseware will be focused on basic injury treatment that is targeted to the student that age 18 to 25 years old. The content for the proposed project has been done surrounding district of UiTM Arau, Perlis. The project has been published or install on standalone computer. The methodology that used is ADDIE Model. ADDIE Model consists of five stages which are analysis phase, design phase, development phase, implementation phase and evaluate phase. The result based on pre-test and post-test was done to evaluate the percentage of the student’s improvement in remembering the basic injury and treatment before and after using the application. The software that used to developed this multimedia application courseware include Adobe Flash Professional CS6, Adobe Photoshop and Wondershare Filmora. The result will produce an attractive multimedia courseware of emergency injury treatment for student. They perform worse on remembering the name of injury and the injuries area. Through this courseware, the student will be able to know the injury symptom and injury name without depend refer the website.